Detection of Adulteration of Milk from Other Species with Cow Milk through an Immersible Photonic Immunosensor - Dimitra Kourti; Michailia Angelopoulou; Konstantinos Misiakos; Eleni Makarona; Anastasios Economou; Panagiota Petrou; Sotirios Kakabakos (Engineering Proceedings, 2023)
Cow milk is more allergenic than milk from other species, and therefore the adulteration of ewe or goat milk with cow milk can pose a serious threat to consumers. In this work, a silicon-based photonic immunosensor, which includes two U-shaped Mach–Zehnder Interferometers (MZIs), was employed for the detection of ewe and goat milk adulteration with cow milk through the immunochemical determination of the milk. The method was fast and sensitive with a detection limit of 0.04 μg/mL bovine k-casein (which corresponds to approximately 0.06% cow milk) in ewe or goat milk, respectively, and with a total assay time of 12 min.